Investigation of water-soluble organic constituents and their spatio-temporal heterogeneity over the Tibetan Plateau. (1st June 2022) - Niu, Hewen; Lu, Xixi; Zhang, Guotao; Sarangi, Chandan
Abstract: Investigating the migration and transformation of carbonaceous and nitrogenous matter in the cryosphere areas is crucial for understanding global biogeochemical cycle and earth's climate system. However, water-soluble organic constituents and their transformation in multiple water bodies are barely investigated. Water-soluble organic carbon (WSOC) and organic nitrogen (WSON), and particulate black carbon (PBC) in multiple types of water bodies in eastern Tibetan Plateau (TP) cryosphere for the first time have been systematically investigated. Statistical results exhibited that from south to north and from east to west of this region, WSOC concentrations in alpine river runoff were gradually elevated. WSOC and nitrogenous matter in the alpine river runoff and precipitation in the glacier region presented distinct seasonal variations. WSON was the dominant component (63.4%) of water-soluble total nitrogen in precipitation over high-altitude southeastern TP cryosphere. Water-soluble carbonaceous matter dominated the carbon cycle in the TP cryosphere, but particulate carbonaceous matter in the alpine river runoff had a small fraction of the cryospheric carbon cycle. Analysis of optical properties illustrated that PBC had a much stronger light absorption ability (MAC-PBC : 2.28 ± 0.37 m 2 g −1 ) than WSOC in the alpine river runoff (0.41 ± 0.26 m 2 g −1 ). Ionic composition was dominated by SO4 2−, NO3 −, and NH4 + (average: 45.13 ± 3.75%) in the snow of glaciers, implying important contribution of (fossil fuel) combustion sources over this region. The results of this study have essential implications for understanding the carbon and nitrogen cycles in high altitude cryosphere regions of the world. Future work should be performed based on more robust in-situ observations and measurements from multiple environmental medium over the cryosphere areas, to ensure ecological protection and high-quality development of the high mountain Asia. Graphical abstract: Image 1 Highlights: WSOC and WSON contents in multiple types of water bodies have been investigated. WSON was the dominant component (63.4%) of rainwater WSTN over the southeastern TP. Post-depositional process has obvious effect on redistribution of WSOC in snowpit. PBC and POC in mountainous river runoff make up a small fraction of carbon cycle. Water-soluble carbonaceous matter dominates the carbon cycle in TP cryosphere.